Staphylococcus aureus vs. Osteoblast: Relationship and Consequences in Osteomyelitis - Josse, Jérôme; Velard, Frédéric; Gangloff, Sophie C. (Frontiers in Cellular and Infection Microbiology, 2015)
Bone cells, namely osteoblasts and osteoclasts work in concert and are responsible for bone extracellular matrix formation and resorption. This homeostasis is, in part, altered during infections by Staphylococcus aureus through the induction of various responses from the osteoblasts. This includes the over-production of chemokines, cytokines and growth factors, thus suggesting a role for these cells in both innate and adaptive immunity. Staphylococcus aureus decreases the activity and viability of osteoblasts, by induction of apoptosis-dependent and independent mechanisms. The tight relationship between osteoclasts and osteoblasts is also modulated by Staphylococcus aureus infection. The present review provides a survey of the relevant literature discussing the important aspects of Staphylococcus aureus and osteoblast interaction as well as the ability for antimicrobial peptides to kill intra-osteoblastic Staphylococcus aureus, hence emphasizing the necessity for new anti-infectious therapeutics.